2016
DOI: 10.1111/cogs.12389
|View full text |Cite
|
Sign up to set email alerts
|

Containment and Support: Core and Complexity in Spatial Language Learning

Abstract: Containment and support have traditionally been assumed to represent universal conceptual foundations for spatial terms. This assumption can be challenged, however: English in and on are applied across a surprisingly broad range of exemplars, and comparable terms in other languages show significant variation in their application. We propose that the broad domains of both containment and support have internal structure that reflects different subtypes, that this structure is reflected in basic spatial term usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…For example, in addition to spatial prepositions, English has spatial verbs, such as "fit, connect" to indicate tight-fit relation (e.g., fit the book into the cover, fit/connect the Lego â piece onto another Lego â ) piece). Such spatial verbs may play some role in categorizing space in English (Fuse, 2006;Landau, Johannes, Skordos, & Papafragou, 2016). Landau et al (2016) have recently shown that English speakers use more diverse verbs to indicate various types of support, in particular those involving attachment or hanging.…”
Section: Linguistic Categorization Of Spatial Relation: a Contrast Bementioning
confidence: 99%
See 4 more Smart Citations
“…For example, in addition to spatial prepositions, English has spatial verbs, such as "fit, connect" to indicate tight-fit relation (e.g., fit the book into the cover, fit/connect the Lego â piece onto another Lego â ) piece). Such spatial verbs may play some role in categorizing space in English (Fuse, 2006;Landau, Johannes, Skordos, & Papafragou, 2016). Landau et al (2016) have recently shown that English speakers use more diverse verbs to indicate various types of support, in particular those involving attachment or hanging.…”
Section: Linguistic Categorization Of Spatial Relation: a Contrast Bementioning
confidence: 99%
“…Such spatial verbs may play some role in categorizing space in English (Fuse, 2006;Landau, Johannes, Skordos, & Papafragou, 2016). Landau et al (2016) have recently shown that English speakers use more diverse verbs to indicate various types of support, in particular those involving attachment or hanging.…”
Section: Linguistic Categorization Of Spatial Relation: a Contrast Bementioning
confidence: 99%
See 3 more Smart Citations